Engaging patients and clinicians through simulation: rebalancing the dynamics of care - Kneebone,R; Weldon,S-M; Bello,F (Advances in Simulation, 2016)
This paper proposes simulation-based enactment of care as an innovative and fruitful means of engaging patients and clinicians to create collaborative solutions to healthcare issues. This use of simulation is a radical departure from traditional transmission models of education and training. Instead, we frame simulation as co-development, through which professionals, patients and publics share their equally (though differently) expert perspectives. The paper argues that a process of participatory design can bring about new insights and that simulation offers understandings that cannot easily be expressed in words. Drawing on more than a decade of our group’s research on simulation and engagement, the paper summarises findings from studies relating to clinician-patient collaboration and proposes a novel approach to address the current need. The paper outlines a mechanism whereby pathways of care are jointly created, shaped, tested and refined by professionals, patients, carers and others who are affected and concerned by clinical care.